(3GdEeGe GHf JjejI hLeGYI GdJHdjZ (B((3GdOYhI(B) /s - (3GdQjS, YHO GdYRjR Hf QjSs; (3GdSOMGf, YHO GdYRjR Hf eMeO Hf YHO Gddg,s 1380 (3gLQj(B-s ((3GdbGgQI (B:s (3YHO GdYRjR GdQjS,s, 2004)
(3JMJhj gPg GdQSGdI Ydi aJhi CMO YTQ YGdeG ef YdeGA GdYUQ cGdTjN eMeO Hf EHQGgje hGdCdHGfj hYajaj ePjdI HQSGdJjf eajOJjf(B.s
Keywords: (3GHf JjejI, CMeO Hf YHO GdMdje Hf YHO GdSdGe,s -- 661-728 (3gLQjs; (3LeGYI GdOYhI hGdJHdjZs; (3GdMQcGJ GdESdGejIs -- (3GdgfOs